Molecular characterization of Spanish autochthonous almond breeding collections using SSRs - Martínez-Gómez P.; Romero A.; Batlle I.; Dicenta F. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
Despite the new almond cultivars released from breeding programs are displacing the autochthonous cultivars in each area, there are a lot of local cultivars that still have a great interest and they are cultivated in the different areas. Some of them are difficult to identify and frequently the same name is given to different cultivars or a genotype is known with different names. These varieties were selected over the years for its adaptation to warm Mediterranean climate and they are a valuable plant genetic resource that must be protected. The objective of this work is the molecular characterization of Spanish autochthonous almond breeding collections using SSRs. Forty two different early flowering and self-incompatible cultivars were assayed using 5 SSRs of reference in almond: BPPCT007, CPPCT005, MA27a, MA40a and UDP96005. Results have showed the great diversity of this autochthonous germplasm and the effectiveness of SSRs by the correct identification, detecting some synonymies and suggesting the origin of some autochthonous cultivars.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)